In‐situ expansion strategy towards hierarchical mesoporous carbon: Formation mechanism and application in supercapacitors. (3rd January 2022) - Guo, Nannan; Luo, Wanxia; Zhou, Doudou; Xu, Mengjiao; Qiu, Daping; Gao, Ang; Ma, Rui; Sheng, Rui; Jia, Dianzeng; Wang, Luxiang
Summary: The microporous carbon with large surface area is widely used in supercapacitors. However, the sluggish ion transport kinetics drastically hampers the practical application. Herein, an efficient in‐situ expansion strategy for the preparation of hierarchically structured mesoporous carbon is developed by the pyrolysis of sodium lignosulfonate with HCOOK. Various techniques including in‐situ methods are employed and the formation mechanism of the hierarchical mesoporous structure is thus clarified. The grain refinement, crystal rearrangement and in‐situ expansion enable the formation of the unique porous carbon with a high mesoporous volume, an interconnected and hierarchical porous structure and a large ion‐accessible specific surface area. The specific capacitance and capacitance retention of the obtained sample reach 436 F g −1 (1 A g −1 ) and 64% at 100 A g −1 in the aqueous electrolyte in a three‐electrode system. Moreover, the obtained sample also shows a high energy density of 41.2 Wh kg −1 in a two‐electrode system using ionic liquid as electrolyte. The novel in‐situ route can be extended to the synthesis of other biomass‐based carbon materials for electrochemical applications. Abstract : An in‐situ activation strategy towards hierarchical mesoporous carbon. The grain refinement, crystal rearrangement and in‐situ expansion enable the formation of the unique porous structure. An excellent capacitance of 436 F g −1 can be achieved in a three‐electrode system. A high energy density of 41.2 Wh kg −1 at 620 W kg −1 is obtained in ionic liquid electrolyte.